Clerodendrum trichotomum Thunb.: a review on phytochemical composition and pharmacological activities - Li, Linzhen; Tang, Zhiyi; Xiao, Shengjia; Dai, Xiangjie; Wang, Yutong; Wei, Xi (Frontiers in Pharmacology, 2025)
Clerodendrum trichotomum Thunb. (C. trichotomum) is a shrub or tree of the genus Clerodendrum, family Lamiaceae, which is widely distributed in China, Korea, India, Japan and Philippines. C. trichotomum is a kind of medicinal and edible plant which integrates ecological afforestation, garden greening, herbal medicine and flavor wild vegetable. As a traditional Chinese medicine, C. trichotomum is used to treat various diseases and conditions, which has inspired research on the pharmacological activities of its different parts, including roots, stems, leaves, flowers and fruits. These studies have revealed many biological properties of C. trichotomum, such as antihypertensive, antitumor, antioxidant, antiinflammatory, antibacterial, analgesic, sedative, anti-HIV-1 and whitening. A total of 164 secondary metabolites were isolated from C. trichotomum, and their structural types were mainly terpenoids, flavonoids, steroids, phenylpropanoids and phenylpropanoid glycosides, phenylethanosides, phenolic glycosides, anthraquinones, polyketones, cyclohexylethanoids, alkaloids and acid amides. The presence of a variety of phytochemicals, especially abietane diterpenes, clerodane diterpenes, phenylpropanoid glycosides and flavonoid glycosides, plays an important role in the activity diversity of this plant. The current study is attempt to comprehensively compile information regarding the phytochemicals and pharmacological activities of C. trichotomum, provide the chemotaxonomic proof for the taxonomic classification of the plant, and also highlight the current gaps and propose possible bridges for the development of C. trichotomum as a therapeutic against important diseases.